A Ratio Type Exponential Estimator for Estimating Finite Population Mean in Double Sampling for Stratification - Bhadauriya, Anupama; Srivastava, Namita; Dhakar, Jagmohan Singh (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
In this paper, we proposed a ratio type exponential estimator for estimating the finite population mean in double sampling for stratification. The bias and mean square error of the proposed estimator are obtained. The proposed estimators have been compared with usual unbiased estimator, Ige Tripathi (1987), Tailor et al. (2014) estimators in double sampling for stratification. The proposed estimator is found to perform better than usual unbiased estimator, Ige Tripathi (1987), Tailor et al. (2014) estimators in double sampling for stratification. To judge the performance of the proposed estimator an empirical study has been carried out.